Leanness level: analysis and systematic literature review - Melo, Julio Cesar [UNESP]; de Souza, Fernando Bernardi [UNESP]; Luiz, Joao Victor Rojas [UNESP]; Luiz, Octaviano Rojas [UNESP]; de Campos, Renato [UNESP] (Inderscience Publishers, 2024)
The success of Toyota, and the spread of lean manufacturing management, has led many companies to deploy the lean philosophy. However, even after the passage of time and human and financial efforts to establish lean practices, such companies have recognised the need to measure their respective leanness levels, as a means of identifying gaps and developing action plans to consolidate its implementation. Aware of this demand, academics have sought to study and develop leanness instruments, utilising techniques and methodologies such as multi-criteria decision-making, statistical calculations, surveys, case studies and the adoption of lean tools and practices, to this end. This article analyses and systematises these instruments as a means of support, as much to future research as to those practitioners who desire to measure their levels of leanness, but have not yet decided which of the instruments available in the literature to use.
Keywords: lean manufacturing; lean production; leanness instruments; systematic review; Toyota Production System; TPS